Dehydrogenation of formic acid using molecular Rh and Ir catalysts immobilized on bipyridine-based covalent triazine frameworks - Gunasekar, Gunniya Hariyanandam; Kim, Honggon; Yoon, Sungho (ROYAL SOC CHEMISTRY, 2019)
In this study, catalytic dehydrogenation of formic acid into H-2/CO2 using half-sandwich Rh(iii)/Ir(iii) catalysts immobilized on variable dimensions of bipyridine-based covalent triazine frameworks (bpy-CTFs) has been described for the first time with a highest initial turnover frequency of 7930 h(-1). A systematic study on the influence of the central metal cation (Rh vs. Ir), CTF architectures and amount of metal loadings on the CTF is presented.
Keywords: HYDROGEN GENERATION; ROOM-TEMPERATURE; CO2; FUTURE; DECOMPOSITION; COMPLEX